Profitability Condition With Stylized Fact of Banking Industries in Indonesia, Malaysia and Thailand - Helma Malini (AFEBI Management and Business Review, 2020)
The survival of banking industries are determined by many factor including profitability earn during the years. Therefore, this study investigates factors affecting profitability of banks in ASEAN. This study uses 10 banks with the largest assets in Indonesia, Malaysia and Thailand with sample studies of 30 banks in ASEAN with 10 years of operationalization duration. Return on assets (ROA) is the dependent variable and the independent variables used are non-performing loans (NPL), capital adequacy ratios (CAR), total assets (Size), loan-to-deposit ratio (LDR), domestic product growth gross (GDP growth), inflation, interest rates and exchange rates. Data is processed using panel data regression with the Cochrance Orcutt method on the basis of the Common and Fixed Effect Model with the combination of stylized facts among each countries. The final results of this study are varied among countries. In Indonesia only NPLs have a significant significance of ROA, which is a significant negative. In Malaysia, only the exchange rate is significant to ROA, which is a significant negative. In Thailand, only NPI has a significant effect on ROA, which is a significant negative. Overall in Southeast Asia, only NPLs, interest rates and exchange rates significantly affect ROA, which is a significant negative. In other independent variables, it does not have a significant effect on ROA.